Birds at the Teutonic Order's castles in Prussia (Poland). (20th July 2022) - Wiejacka, Martyna; Makowiecki, Daniel; Opelkova, Monika; Wiewióra, Marcin; Pluskowski, Aleks
Abstract: The article is the first presentation of detailed research of bird bones from six Teutonic Order castles built in the 13th century in the historical territory of Prussia, mainly in Terra Culmensis – the Kulmerland. The aim was to assess diachronic trends in bird exploitation at these sites. 28 different species were identified within the three historical periods represented in the occupation phases of these castles – the Pre-Teutonic Order or early medieval period, the Teutonic Order's period of rule and that of the Kingdom of Poland. The most numerous were domestic fowl (chicken) and geese, and their anatomical composition, age, sex and biometrics are described. A small percentage consists of wild species. The significance of birds for the castle elites in all periods was assessed through a comparison of archaeo-ornithological and historical data. The bird remains (and eggshells) from these castles largely represent the waste from food preparation, but some can be connected with hawking, the use of feathers and down, as well as for particular species kept for ornamental purposes. All of these are defining characteristics of high-status sites in the medieval and early modern periods.